A Supramolecular Approach for Enhanced Antibacterial Activity and Extended Shelf-life of Fluoroquinolone Drugs with Cucurbit[7]uril - El-Sheshtawy, Hamdy S. (Sci Rep, 2018)
The host-guest interactions of a third-generation fluoroquinone, danofloxacin (DOFL), with the macrocyclic host cucurbit[7]uril (CB7) have been investigated at different pH values (~3.5, 7.5, and 10). The photophysical properties have been positively affected, that is, the fluorescence yield and lifetime increased, as well as the photostability of DOFL improved in the presence of CB7. The antibacterial activity of DOFL is enhanced in the presence of CB7, as tested against four pathogenic bacteria; highest activity has been found towards B. cereus and E. coli, and lower activity towards S. aureus and S. typhi. The antibacterial activity of two additional second-generation fluoroquinones, i.e., norfloxacin and ofloxacin, has also been investigated in the absence as well as the presence of CB7 and compared with that of DOFL. In case of all drugs, the minimum inhibitory concentration (MIC) was reduced 3–5 fold in the presence of CB7. The extended shelf-life (antibacterial activity over time) of the fluoroquinone drugs in the presence of CB7, irrespective of four types of bacteria, can be attributed to the enhanced photostability of their CB7 complexes, which can act as better antibiotics with a longer expiry date than uncomplexed DOFL.